The Influence of Grain Prices on Rice Farming Business Income in Ngrandulor Peterongan Village, Jombang - Meisa Muqtadhiroh Purwanti; Heru Totok Tri Wahono (INCOME: Innovation of Economics and Management, 2024)
This research aims to analyze the influence of grain prices on rice farming income in Ngrandulor Village, Peterongan, Jombang. The research method used was a survey with a sampling technique that suited the characteristics of the rice farmer population, with a sample size of 30 respondents. Data is collected through questionnaires and direct interviews, then analyzed using appropriate statistical methods, such as simple linear regression or multiple linear regression, depending on the variables analyzed. The research results show that the price of grain has a significant influence on rice farming income. Data analysis indicates that there is a positive and significant relationship between grain prices and rice farming income. In other words, the higher the price of grain, the higher the income of rice farming businesses. The conclusion of this research is that the price of grain is an important factor that can influence the income of rice farmers, so the stability of grain prices needs to be maintained to improve farmers' welfare.